1996
DOI: 10.1104/pp.112.2.503
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Expression of 1-Aminocyclopropane-1-Carboxylate Oxidase mRNA following Pollination of Immature and Mature Petunia Flowers

Abstract: Pollination of petunia (Petunia hybrida) flowers induces a rapid increase in ethylene production by styles, which subsequently leads to increased ethylene production by the corolla, inducing senescence. We have investigated the temporal and spatial expression of 1-aminocyclopropane-1-carboxylate (ACC) oxidase transcripts in petunia styles in an attempt to elucidate its role in increased ethylene biosynthesis following pollination. Previously, we reported that the development of petunia flowers was associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 16 publications
2
44
1
Order By: Relevance
“…In carnation, orchid, and petunia flowers, such pollination-induced ethylene production is associated with the expression of ACC synthase and ACC oxidase genes (Woodson et al, 1992;O'Neill et al, 1993;Tang and Woodson, 1996;O'Neill and Nadeau, 1997). However, the nature of pollen-pistil interactions leading to the expression of ACC synthase genes in floral organs is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…In carnation, orchid, and petunia flowers, such pollination-induced ethylene production is associated with the expression of ACC synthase and ACC oxidase genes (Woodson et al, 1992;O'Neill et al, 1993;Tang and Woodson, 1996;O'Neill and Nadeau, 1997). However, the nature of pollen-pistil interactions leading to the expression of ACC synthase genes in floral organs is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that a decrease of PhEIN2 mRNA in the petal tube is sufficient to delay flower senescence, and a decrease in the petal limb gives additional longevity to flowers. It has been suggested that the ethylene produced from pistils triggers ethylene production in petals after pollination (Tang and Woodson, 1996). Ethylene perception in the petal tube appears to be essential for the subsequent induction of petal senescence.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ethylene induces flower senescence in petunia (Gilissen and Hoekstra, 1984;Tang and Woodson, 1996), and reduced ethylene sensitivity results in a significant delay in flower senescence after ethylene treatment and pollination in etr-44568 petunia (Wilkinson et al, 1997; Table I). The PhEIN2 transgenic plants showed a significant delay in flower senescence in the T0 and T1 progeny after ethylene treatment and pollination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of positive feedback regulation in ethylene biosynthesis has been elucidated at the molecular level for ACC synthase and/or ACC oxidase in plants such as carnation (Jones andWoodson, 1997), orchid (O'Neill et al, 1993), and petunia (Tang and Woodson, 1996) flowers and mung bean (Kim and Yang, 1994) and pea (Peck and Kende, 1995) seedlings. The negative feedback regulation of ethylene biosynthesis at the molecular level has been reported in winter squash fruit (Nakajima et al, 1990), mung bean seedlings Yoon et al, 1997), transgenic petunia flowers (Wilkinson et al, 1997), and leaves of the tomato cv Never ripe (Lund et al, 1998).…”
mentioning
confidence: 99%